The morphology of the arteries originating from the arcus aorta and the branches of these arteries in mole-rats (Spalax leucodon) - Aydin, A.; Ozkan, Z. E.; Ilgun, R. (Czech Academy Agricultural Sciences, 2013)
In this study, the aim was to investigate the anatomy of the aortic arch arteries in mole-rats (Spa lax leucodon). Six adult mole-rats were used for this purpose. Coloured latex was injected into the left ventriculus of the hearts of all animals. The materials were carefully dissected and the arterial patterns of arteries originating from the aortic arch were examined. The brachiocephalic trunk, the left common carotid and the left subclavian arteries were detached from the aortic arch. The brachiocephalic trunk separated into the right subclavian and common carotid arteries. The branches separating from the subclavian arteries were on the right, the common branch giving the profund cervical, the internal thoracic, and the costocervical trunk, and on the left the internal thoracic and the costocervical trunk were in the common root and the profund cervical artery was independent and on both sides after giving the common branch of the superficial servical and the external thoracic artery. This continued as the axillary artery which was then separated into the subscapular and the brachial arteries. Thus, the arteries originating from the aortic arch and the branches of these arteries were found to be different from other rodents and domestic mammals.
Keywords: arteries; aortic arch; mole-rats (Spalax leucodon)